2020
DOI: 10.1186/s12916-020-01597-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of physical distance measures on the transmission of COVID-19 in the UK

Abstract: Background: To mitigate and slow the spread of COVID-19, many countries have adopted unprecedented physical distancing policies, including the UK. We evaluate whether these measures might be sufficient to control the epidemic by estimating their impact on the reproduction number (R 0 , the average number of secondary cases generated per case). Methods: We asked a representative sample of UK adults about their contact patterns on the previous day. The questionnaire was conducted online via email recruitment and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
441
1
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 620 publications
(493 citation statements)
references
References 28 publications
39
441
1
12
Order By: Relevance
“…mixing as well the impact of control measures such as quarantine, travel restrictions or social distance measures, or lockdown in general [4][5][6]. Previous work from the UK suggests that lockdown measures may have decreased the reproduction number from 2.6 to 0.62 [6]. Similarly, researchers from China have shown a significant decrease of the reproduction number below one following physical restriction measures [7].…”
Section: Plos Onementioning
confidence: 99%
“…mixing as well the impact of control measures such as quarantine, travel restrictions or social distance measures, or lockdown in general [4][5][6]. Previous work from the UK suggests that lockdown measures may have decreased the reproduction number from 2.6 to 0.62 [6]. Similarly, researchers from China have shown a significant decrease of the reproduction number below one following physical restriction measures [7].…”
Section: Plos Onementioning
confidence: 99%
“…This may strengthen the conclusion that social distancing resulted in the strongest decrease in incidence rate in most densely populated areas. Although adherence to these distancing rules seems high, 14 it is unknown whether there is a relationship between adherence and population density.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Studies on the US and UK concluded that introducing social distancing regulations reduced contact rate and physical proximity to others, resulting in reductions in COVID-19 incidence rates. 14,16 Since areas with high population density tend to have or be close to major airports or travel hubs, regulations restricting mobility might have resulted in a stronger reduction in incidence rate within these areas.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…The population-level adherence to such measures may determine to a considerable extent the national magnitude and duration of the COVID-19 pandemic [6,7]. However, little is known on population-level adherence to the various containment measures implemented worldwide, with most studies focusing on adherence to hygiene measures among healthcare workers [8,9,10].…”
Section: Introductionmentioning
confidence: 99%